Curriculum Evaluation of Islamic Elementary Teacher Education Programs in Indonesia - Fauzan, Fauzan (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2022)
AbstractFrom the Indonesian National Qualifications Framework (KKNI) perspective, each study program should be able to present itself with the “graduate profile” obtained through tracer study activities, feasibility studies and needs analysis in the community. The graduate profile must at least reflect abilities that refer to four aspects of needs (1) attitude, (2) knowledge, (3) general skills; and (4) special skills. The four abilities are translated into a learning outcome (learning outcome) in each course in the study program. Thus, all learning plans or Semester Learning Plans should be based on learning outcomes (learning outcomes) following the needs of the graduate profile. This study aims to evaluate the readiness of the Islamic Elementary Teacher Education study program in Indonesia to implement the current curriculum policy, called the Indonesian National Qualification Framework. This study follows a mixed-method research design by undertaking an evaluation study. Moreover, the data were collected through a literature study, document study, questionnaire, and interview. Twenty-one departments were analysed, involving seventeen state and four private universities. This study provided some noteworthy findings, one of which is to measure how much the readiness of programme directors to implement new policies.AbstrakDari perspektif Kerangka Kualifikasi Nasional Indonesia (KKNI), setiap program studi harus dapat mempresentasikan dirinya sendiri dengan